Penjenjangan Kemampuan Berpikir Kritis Matematis Berdasarkan Teori Bloom Ditinjau Dari Kecerdasan Multiple Intelligences - Mujib, Mujib (Desimal: Jurnal Matematika, 2019)
This study aims to see how the mathematical model of critical thinking skills is based on Bloom theory in terms of Multiple Intelligences intelligence, namely Students have Linguistic Intelligences, Logical-Mathematical and Spatial Intelligence Intelligence. The research method used is descriptive qualitative. Subjects taken in this study were using purpose sampling techniques. Data collection techniques used are tests, questionnaires, observation and interviews. Data analysis was carried out in a qualitative descriptive manner. Each Multiple Intelligences intelligence is capable of observing, understanding, applying, analyzing, evaluating and creating. Based on the tests and interviews the characteristics seen are at the stage of observing, understanding and applying. Not able to analyze, evaluate and be creative. Students who have a tendency to Linguistic Intelligence Intelligence processes the process of critical thinking mathematically has the stages of Lower Order Thinking (LOT). Students who have Spatial Intelligence Intelligence stages of critical thinking skills are mathematical, namely at the stage of observing, understanding, applying analysis and evaluation. At the stage of creation, the characteristics of students are not able. Students who have a tendency for Spatial Intelligence intelligence in the process of mathematical critical thinking skills at the level of Middle Order Thinking (MOT). Students who have the type of Logical-mathematical Intelligence Intelligence stage of critical thinking ability that is the stage of observing, understanding, applying, analyzing, evaluating, and developing. Students who have the type of Logical-mathematical Intelligence tendencies in the process of mathematical critical thinking abilities at the stages of Higher Order Thinking (HOT).